METHODS OF TEACHING THE TOPIC OF THE SQUARE EQUATION IN 8TH GRADE ALGEBRA LESSONS AND BUILDING SKILLS IN STUDENTS (Web of Teachers: Inderscience Research, 2024)
This article focuses on the simple ways to explain the "quadratic equations" to students in the 8th grade textbook, as well as the formation of students' skills on a new topic.